The status and role of provincial governance in the South African constitutional dispensation 1996 - 2012 - Diseko, Mogale Daniel (University of the Free State, 2018)
Provincial governance in South Africa has come under tremendous pressure and scrutiny from a variety of sectors, including Chapter 9 institutions, non-governmental organisations, the media, and opposition political parties. However, these challenges are not new and have been a concern for the South African government since the dawn of democracy. Former president, Thabo Mbeki, during his term of office, highlighted the challenges facing provinces – particularly with regard to financial management – and hinted at the need to abolish provinces. Endemic poor governance and incapacity within provinces – particularly those that inherited regions of the former homelands – undermined government’s efforts of reconstruction and development. Yet, more than 23 years since the dawn of democracy in the country, the provinces continue to struggle to fulfil their executive obligations. This incapacity at provincial government level has led the ruling ANC to review provinces. The review of provinces requires constitutional amendment as it entails rearranging the political legislative framework and system of government that assigns the powers and functions to the provinces; a political provision that is entrenched in the Constitution of the country. This political framework of government, known as a quasi-federal system or a decentralised unitary state because of its close resemblance to a federal state, albeit highly centralised, was agreed to as a compromise by negotiating parties during the Codesa negotiations to accommodate the fears and safeguard the interests of minority parties, particularly the IFP and the NP, in the new government of national unity. The study took an exploratory descriptive qualitative research approach to explore the status and role of provincial governance in the South African constitutional dispensation between 1996 and 2012. The study found weaknesses in the legislative framework of the current political system of government, which subsequently renders provinces prone to practices of poor governance and incapacity with respect to their ability to fulfil their constitutional executive obligations and electoral mandate. Thus, the study proposes an assignment of constitutionally guaranteed powers and functions to provinces through constitutional reforms. This would establish South Africa as a federation, whereby provinces have the authority and capacity to act independently as autonomous institutions of democratic governance within their respective jurisdictions to fulfil their legislative and executive obligations in the best interest of their diverse constituencies.
Thesis (Ph.D. (Governance and Political Transformation))--University of the Free State, 2018
Keywords: Structure of government; Intergovernmental relations; Federalism; Centralisation; Decentralisation; Sub-national government; Constitution; Provincial government; Powers and functions; South Africa; Governance; Fiscal autonomy